The equivalent expression to the given one is -sin(pi/6).
The given expression is:
sin(7pi/6)
Where the argument is in radians.
Remember that:
sin(a + b) = sin(a)*cos(b) + sin(b)*cos(a)
Now we can rewrite:
sin(7pi/6) = sin(pi + pi/6)
Then we can use the above relation to rewrite:
sin(pi + pi/6) = sin(pi)*cos( pi/6) + sin(pi/6)*cos(pi)
And we know that:
sin(pi) = 0
cos(pi) = -1
Then we can write:
sin(7pi/6) = - sin(pi/6)
If you want to learn more about the sine function:
https://brainly.com/question/9565966
#SPJ4